Cellular retinoic acid binding protein 2 inhibits osteogenic differentiation by modulating LIMK1 in C2C12 cells. (9th October 2015) - Wang, Rui; Yang, Qingyuan; Xiao, Weifan; Si, Ruirui; Sun, Fenyong; Pan, Qiuhui
<x xml:space="preserve">Abstract</x> Cellular retinoic acid binding protein 2 (CRABP2) is essential for myoblast differentiation, however, little is known about its role in osteogenic differentiation. This study mainly aims to explore the biological functions and the underlying molecular mechanisms of CRABP2 in osteogenesis. Using quantitative polymerase chain reaction and western blot assays, we found that the expression of CRABP2 at both mRNA and protein levels were downregulated during osteogenesis. Furthermore, CRABP2 knockdown displayed significant changes in the cell phenotype and the actin filaments (F‐actin) polymerization in C2C12 cells treated with BMP2. Moreover, the western blotting of osteogenic differentiation biomarkers, alkaline phosphatase (ALP) staining and Alizarin red staining showed that CRABP2 dramatically inhibited osteogenic differentiation. The following investigation of molecular mechanisms implicated that CARBP2 specifically interacted with LIMK1, a key factor in acin cytoskeletal rearrangements in osteogenesis, to interrupt its activity and stability in an ubiquitin‐proteasome pathway to prevent C2C12 cells from osteogenic differentiation in response to BMP2. Above all, our data suggest a novel function of CRABP2 in regulating actin remodeling and osteogenic differentiation via LIMK1, thus presenting a possible molecular target for promoting the osteogenic differentiation in bone degenerative diseases.